EFESIENSI PENGELOLAAN WAKAF TUNAI - Nur Ahmad Ricky Rudianto; Himmatul Ulyah (Budgeting: Jurnal Akuntansi Syariah, 2021)
This research focuses on efficient cash waqf management conducted qualitatively using library studies. The approach in this research is a critical analytical descriptive approach. The data used is sourced from sekuder data obtained from the results of research that has been done before, articles and reference books with subjects about waqf and cash waqf. The object studied is the management of waqf carried out at Islamic Financial Institutions (LKS), Non-Profit Institutions and the Government. Based on the literature review that has been done, it is found that the most efficient waqf management if managed by Islamic Financial Institutions (LKS), This is because Islamic Financial Institutions have clear functions and duties, competent human resources, guaranteed accountability and the breadth of the network in the management of waqf funds to be channeled and invested.